Becoming a Muslim in Japan : The Journey of Faith and Identity - Kocalan, Elif Büşra (Religion and the Social Order, 2026)
What draws someone to Islam in a country where few people even know a Muslim? In Becoming a Muslim in Japan , you meet 62 Japanese converts whose journeys defy common assumptions. Their stories are not about crisis, but curiosity. They speak of unexpected encounters, moments of reflection, or quiet admiration that gradually deepened into faith. Based on immersive fieldwork and interviews, this book shows how Islam is not adapted in isolation but interwoven with Japanese values. If you are interested in religion, identity, or cultural transformation, this book offers rare access to spiritual lives shaped across boundaries - personal, cultural, and national.